The effect of the Technical Risks on the successful implementation of BIM - ASSAF, OBAID MHD DEIA ELDIN (2019)
"The digital revolution had many applications in different industries which lead to a major improvement. So it was necessary to use BIM as a new technology in the construction field for ensuring a rapid and stable growth. There are many challenges in implementing BIM in the construction industry which threaten its success and prevent the use of all advantages. There are many potential technical risks associated with the use of BIM technology which negatively impacted different aspects in the construction industry. There are four major technical risks categories considered in this research which are technical risks related to interoperability issues, dealing with data, intricacy and missing quality. Each category of these risks has different variables which affect BIM process and functionality in different phases of the projects. This study will focus on analyzing the technical risks variables and its impact on the success of BIM use on the construction field. The first part of this research was the qualitative part where it build the analysis on previous studies on these technical risks. The qualitative was followed by forming a questionnaire to collect the information from the participants on BIM technical risks. A collected responses from the participants was equal 72 which have completed all the questions on the questionnaires. All the responses were analyzed the statistical software (SPSS) by applying different statistical tests like descriptive, reliability, ANOVA and Tukey which will help in interpreting the participants answers. The outcomes in the research indicate that there generally no significance difference in the responses of the participants in this study which agreed about the negative impact of the technical risks variables on the use of BIM. The technical risks variables affecting the quality and speed of BIM process and modeling function which cause delay and cost increase on the construction projects. Thus, future researches are encouraged to be done on this field to encounter deeper study of the impact of these technical risks variables on the effect of new virgins of BIM platforms. Additionally, future researches are recommended to consider the technical risks effect on the construction projects in order to update other studies about the mitigations measures to reduce the negative effect. "